Selected studies in the diagnosis of pulmonary embolism - review - Maciej Kozioł; Piotr Piech; Paweł Obierzyński; Grzegorz Staśkiewicz; Grzegorz Opielak; Robert Jan Łuczyk (Kazimierz Wielki University, 2018)
INTRODUCTION Pulmonary embolism (PE) is the result of the narrowing or occlusion of the pulmonary artery or its branches by thrombotic material, which are most often thrombi originating from deep veins of the lower limbs or pelvis. Pulmonary embolism very quickly develops life-threatening symptoms, which is why rapid diagnostics and the implementation of appropriate treatment are particularly important. AIM OF THE STUDY The aim of the following study is to summarize the state of knowledge about the effectiveness of selected methods in the diagnosis of pulmonary embolism. STATE OF KNOWLEDGE In diagnostic strategies regarding pulmonary embolism, the clinical probability of disease, D-dimer concentration, angio-CT examination and lung scintigraphy play a key role. Determining the clinical probability of the disease in combination with the determination of D-dimer concentration allows safe exclusion of pulmonary embolism in a significant percentage of patients. In the analyzed studies, attention was drawn to the large negative predictive value of such a procedure and the necessity to choose an appropriate scale, adjusted to the incidence of PE in a given area. The dissemination of multi-row computed tomography has made it a method of choice in the assessment of pulmonary vessels in the event of suspected pulmonary embolism. In the analyzed studies, attention was paid to the high negative predictive value of angio-CT, in particular in connection with the determination of clinical probability and the determination of D-dimer concentration. However, it may be controversial to choose a procedure for patients with high clinical probability of PE and a negative result of angio-CT. Scintigraphy is considered safe for patients due to the significant reduction of exposure to radiation - low enough that this method could be used also in pregnant women. Analyzed studies have proven that scintigraphy is as effective and safe in excluding pulmonary embolism as computed tomography, and its use may result in the development of new, automated methods for diagnosing pulmonary embolism. SUMMARY The dissemination of factors predisposing to pulmonary embolism made it one of the main causes of mortality, morbidity and hospitalization in Europe [4]. The increased risk of PE affects people over 40 and doubles in every subsequent decade, which means that, in an ageing European society, both the incidence and mortality will increase [6]. Due to non-specific signs and symptoms, which may indicate other diseases it is vital to introduce fast and safe diagnostics which may confirm or rule out pulmonary embolism.